When Eating Becomes a Challenge: A Cross-Sectional Study of Picky Eating Behaviours and Parental Nutritional Practices in Young Children - KHALID, HAMNA; KHAN, KHUSHBAKHT; KALEEM, SUSEN HIRA; RAZAQ, NOSHABA; GHAURI, LAIBA IRFAN; TAREEN, TAMSEELA GUL; FATIMA, SAJJAL (Pakistan Journal of Medical & Health Sciences, 2026)
Purpose; The focus of this research is on the following three hypotheses: (1) Children who are underweight are more food fussy and exhibit more emotional overeating than their normal weight/overweight/obese fellows; (2) Implementing positive parental nutrition practices more frequently leads to a decrease in food fussiness; (3) The level of food fussiness has a negative correlation with positive parental practices and a positive correlation with coercive practices. Methodology: The research employed a cross-sectional methodology during the period of January to June in the year 2025. The research was centered in 3 public schools located in the region of Wah Cantt, Punjab, Pakistan. The participants of the research included 360 children between the ages of 3 and 6 along with their primary caregivers. These research participants were obtained through a randomized sampling technique. The research employed a number of validated and culturally adapted instruments, notably the Child Eating Behavior Questionnaire (CEBQ) and the Parental Feeding Styles Questionnaire (PFSQ), for the collection of the needed data. Relevant anthropometric data was also collected and used in the calculation of the BMI-for-age Z-scores of the children. The research data was processed and analyzed using one-way ANOVA, paired t-tests, and Pearson correlation. The p-value was set at p < 0.05 to determine the level of significance. Results: Among the different BMI categories, underweight children experienced the highest levels of food fussiness (M = 2.47) and emotional overeating (M = 2.48) with these behaviors decreasing as BMI increased. Differences in the level of food fussiness and emotional overeating were statistically significant (food fussiness: F (3, 356) = 16.99, p < .001, η² = .125; emotional overeating: F (3, 356) = 37.63, p < .001, η² = .240). Children whose parents practiced positive feeding more frequently had statistically significant lower food fussiness scores (M = 2.00) in comparison to those whose parents practiced positive feeding less frequently (M = 2.28), t (358) = 3.618, p < .001, Cohen’s d = 0.379. The degree of food fussiness was negatively correlated with positive feeding (r = -0.188, p < .01) and positively correlated with coercive feeding (r = 0.210, p < .01). A strong inverse correlation was also identified between positive and coercive feeding (r = -0.534, p < .01). Conclusion: The results show that lower BMI in preschoolers is linked to greater picky eating and emotional over eating. Positive parental practices in nutrition reduces picky eating, while coercive parental nutrition practices increases picky eating. These findings reinforce the case for parental targeted approaches to nutrition counselling in early childhood in Pakistan.